EP.WE.726A snapshot audit of cholecystectomy for gallstone pancreatitis during the first wave of COVID-19. (28th October 2021) - David, Bryony; Aiynattu, Sony; Jones, Katie; Gallucci, Antonio
Abstract: Aims: COVID-19 has caused difficulties in providing efficient surgical care. We aimed to audit cholecystectomy provision for gallstone pancreatitis from January 2019 to June 2020. We audited time from admission with gallstone pancreatitis to cholecystectomy in pre-COVID and COVID cohorts in order to assess the effect of the first wave of the pandemic on service provision. Methods: Patients with confirmed gallstone pancreatitis plus their age and gender were included using information software Cerner. We analysed length of stay, time to surgery and number of patients planned for surgery. We also looked at readmissions whilst awaiting surgery. Patients with previous cholecystectomies or deemed not fit for surgery were excluded. Results: 68 patients were included; 42 admitted from Jan 2019 to Feb 2020 (non-COVID group) and 26 from March 2020 to June 2020 (COVID 19 group). Average length of stay was 11.8 days for non-COVID group and 8.8 days for COVID group. Average time to surgery for non-COVID group was 47.4 days. 25 patients underwent surgery. Average time to surgery was 56.7 days and 9 patients received surgery, in the COVID group. In this group, 3 patients had index admission surgery compared to 15 in the non-COVID group. Conclusions: Albeit small, our data set shows a longer wait to surgery in the COVID group with fewer operations performed at index admission, compared to the non-COVID group. Future surgical services will require careful planning to ensure that urgent cholecystectomies continue to be performed in acute gallstone pancreatitis.